2006
DOI: 10.1017/bjn20061969
|View full text |Cite
|
Sign up to set email alerts
|

No effect of increased water intake on blood viscosity and cardiovascular risk factors

Abstract: Observational data have suggested that increased water intake decreases the risk of CHD. A postulated mechanism is that increased water ingestion reduces blood viscosity. The aim of the present study was to assess the effect of increased fluid intake on blood viscosity. Men (n 67) and postmenopausal women (n 27) with one or more risk factors for CVD who reported intake of #0·5 litres water daily were randomised to a control group (n 31), an intervention group (n 32) that increased their daily water intake by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…There is some evidence that dehydration might contribute to increased blood viscosity [60,61], a known risk factor for ischemic heart disease and stroke [62,63]. However, several interventions have failed to reduce blood viscosity with greater fluid intake [60,61,64,65] — possibly because a benefit of greater water intake may not be realized in patients who are adequately hydrated, as appeared to be the case in one trial, where the baseline urine volume of patients was ∼1.6 l/day [65]. Few studies have evaluated the direct effect of water intake on cardiovascular outcomes, and these have produced equivocal results.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that dehydration might contribute to increased blood viscosity [60,61], a known risk factor for ischemic heart disease and stroke [62,63]. However, several interventions have failed to reduce blood viscosity with greater fluid intake [60,61,64,65] — possibly because a benefit of greater water intake may not be realized in patients who are adequately hydrated, as appeared to be the case in one trial, where the baseline urine volume of patients was ∼1.6 l/day [65]. Few studies have evaluated the direct effect of water intake on cardiovascular outcomes, and these have produced equivocal results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that water consumption at night can attenuate nocturnal increase in blood viscosity, and therefore, can prevent morning occurrence of cerebral infarction (9) . Some investigators reported a decrease in blood viscosity with increased water intake (9,13,14) , while others reported no changes in blood haemorheology and chemistry with increased water intake (15) . Only one cohort study analysed the effect of water intake and other fluid intake on fatal CHD (1) .…”
mentioning
confidence: 99%
“…Table 3 : RCTs comparing water with other drinks or no drink (eight studies); [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the study populations investigated, we included four studies with type 2 diabetes [ 19 , 22 , 23 , 24 ], three with overweight or obese [ 17 , 18 , 21 ], three with moderately elevated cholesterol [ 26 , 27 , 29 ], one with at least one CVRF [ 20 ] and four with healthy participants [ 16 , 25 , 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%